2021
DOI: 10.1088/1757-899x/1047/1/012089
|View full text |Cite
|
Sign up to set email alerts
|

Building communication networks: on the application of the Kruskal’s algorithm in the problems of large dimensions

Abstract: The paper deals with the development of the topology of ultra-large communication networks, i.e. networks containing several thousand vertices. In this case, the coordinates of the vertices of the undirected graph are somehow predetermined and a set of edges must be constructed. The main point of the options we are considering for developing the network topology is the minimum of the sum of weights of the edges; however, we note in advance that this criterion of minimality is often not the only objective funct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 3 publications
0
2
0
1
Order By: Relevance
“…Berdasarkan penelitian yang dilakukan oleh Nathaniel Akpofure yang telah membuat aplikasi dalam menentukan jarak dalam suatu perusahaan dengan algoritma Dijkstra yang memiliki keunggulan yakni dapat menemukan rute terdekat, membantu pilihan jalur, mengurangi visibilitas pengiriman, menghemat waktu, serta memaksimalkan keuntungan perusahaan (Akpofure & Paul, 2017). Penerapan algoritma Kruskal telah dilakukan oleh B. F. Melnikov dkk yang meneliti algoritma Kruskal dengan dimensi yang besar yang meneliti dengan jumlah titik 512 sampai 8192 dengan hasil total dari waktu eksekusi algoritma dengan jumlah simpul terdekat yang dipakai adalah 10 hingga 40 hal tersebut digunakan untuk pemecahan masalah penjual keliling (Melnikov & Terentyeva, 2021).…”
Section: Pendahuluanunclassified
“…Berdasarkan penelitian yang dilakukan oleh Nathaniel Akpofure yang telah membuat aplikasi dalam menentukan jarak dalam suatu perusahaan dengan algoritma Dijkstra yang memiliki keunggulan yakni dapat menemukan rute terdekat, membantu pilihan jalur, mengurangi visibilitas pengiriman, menghemat waktu, serta memaksimalkan keuntungan perusahaan (Akpofure & Paul, 2017). Penerapan algoritma Kruskal telah dilakukan oleh B. F. Melnikov dkk yang meneliti algoritma Kruskal dengan dimensi yang besar yang meneliti dengan jumlah titik 512 sampai 8192 dengan hasil total dari waktu eksekusi algoritma dengan jumlah simpul terdekat yang dipakai adalah 10 hingga 40 hal tersebut digunakan untuk pemecahan masalah penjual keliling (Melnikov & Terentyeva, 2021).…”
Section: Pendahuluanunclassified
“…In this paper, we revisit algorithm variants that do not rely on the branches and boundaries method, despite prior successful results. Our recent research, particularly in graph theory and ultra-large communication networks, has shown that improving auxiliary heuristics of this method may not always lead to B. F. Melnikov et al Journal of Biosciences and Medicines significant algorithm quality improvements (see [12]). Instead, we focus solely on enhancing the greedy function formulation of the method's algorithms, which we consider auxiliary.…”
Section: Introductionmentioning
confidence: 99%
“…Despite the previously successful results of calculations, we return in this paper to the algorithm variants that do not use the branches and boundaries method: as our recent work has shown (primarily in the subject areas related to graph theory and the development of ultra-large communication networks, [Melnikov and Terentyeva, 2021] etc. ), even greater improvement in the quality of the algorithm can often be achieved without improving the auxiliary heuristics of the branches and boundaries method.…”
Section: Introductionmentioning
confidence: 99%